Network pharmacology, molecular docking and in vivo study on oleanolic acid against psoriasis - Zan, Xuejuan; Zhang, Shunying; Liu, Qikun; Wang, Fang; Tian, Maogui; Cao, Yu (Frontiers in Medicine, 2025)
BackgroundPsoriasis remains incurable, driving the need for new treatments. This study evaluated the therapeutic effects of oleanolic acid on IMQ-induced psoriasis model mice and used network pharmacology and molecular docking to predict its mechanism of action.MethodsThis study assessed the different concentrations (1%, 5%, 10%) of oleanolic acid cream effects on IMQ-induced psoriasis in female BALB/c mice, evaluating therapeutic outcomes via PASI scores, skin lesion staining, and inflammatory factor detection. Network pharmacology and molecular docking predicted OA’s mechanism. Key targets were identified using databases and software analyses.ResultsOleanolic acid can treat skin damage in psoriasis model mice and improve systemic inflammatory responses. Network pharmacology results identified important potential targets for OA treatment of psoriasis, including HSP90AA1, STAT3, MAPK3, HSP90AB1, PPARG, PTGS2, AR, CDK1. GO functional enrichment analysis involved biological functions such as inflammation response, signal transduction, G protein-coupled receptor signaling pathway, etc. KEGG pathway enrichment analysis involved signaling pathways such as neuroactive ligand-receptor interaction, PPAR signaling pathway, Th17 cell differentiation, etc. Molecular docking results showed good affinity between oleanolic acid and MAPK3, STAT3, AR, PPARG.ConclusionOleanolic acid has therapeutic effects on psoriasis, with possible target points being MAPK3, STAT3, AR, and PPARG, involving processes such as inflammation response, negative regulation of cell proliferation, and Th17 cell differentiation.